STATE OF HUMORAL IMMUNITY IN PATIENTS WITH ATYPICAL PNEUMONIA IN FREQUENTLY ILL CHILDREN. - Ibragimova Marina Fedorovna; Shavkatova Zilola Shobiddin kizi (Research Focus International Scientific Journal, 2023)
Atypical pneumonia remains one of the most common and severe diseases of the respiratory system in children [8]. Understanding the pathogenetic role of immune status can contribute to a deeper understanding of the mechanisms of disease development in atypical pneumonia, to develop effective strategies for diagnosing and treating the disease in frequently ill children. Questions regarding the study of the role of immune mechanisms in children with pneumonia and in the formation of a group of frequently ill children are quite controversial and insufficiently reflected, further study of which seems relevant. Currently, convincing data have been accumulated on the important role of the immune system in the formation and development of pneumonia in children In our country, large-scale activities are being carried out for early diagnosis and prevention of somatic diseases among children, especially bronchopulmonary pathology.